MAAT: Multisensorial Audiobooks Authoring Tool - Okuno, Helder Yukio; Carvalho, Flavio; Guedes, Gustavo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2021: Proceedings of the 27th Brazilian Symposium on Multimedia and the Web, 2021)
Multisensory books and audiobooks provide users with greater immersion by stimulating multiple human senses simultaneously during the reading process. A multisensory story contains annotations of effects synchronizing each sensorial stimulus to traditional media, and the manual authoring of these annotations is a costly and time-consuming task. While there are authoring tools to synchronize multisensory effects with videos, there are no authoring tools available for multisensory audiobooks, to the best of our knowledge. This article proposes an authoring tool for multisensory audiobooks called MAAT. It presents the evaluation of MAAT's QoE aspects and compatibility assessments on the file generated by the MAAT tool and on the synchronization of multisensory effects.